Molecular cloning and sequence analysis of an inulinase gene from and Aspergillus sp. - Shamsuddin, Raba'atun Adawiyah; Mustafa, Shuhaimi; Abd. Manap, Mohd. Yazid; Ali, Abdul Manaf; Noormi, Rosli; Subramaniam, Sreeramanan (Springer Netherlands, 2011)
Selected endophytic fungi have been report to be inulin degraders to produce fructose or other oligosaccharides. In this study, the Aspergillus sp. producing inulinase were isolated from selected plant species at Serdang area in Malaysia. Fungal isolates were screened solely based on inulin degrading enzymes production and two isolates named Asf1 and Onf1 were selected as the best inulinase enzyme producers. Genomic DNA of these two isolates were extracted and amplified by polymerase chain reaction (PCR). A 1,341 bp DNA fragment containing inulinase gene was successfully amplified from Asf1 fungal isolate and was named as inu2 gene in this study. Based on the morphological characteristics, rDNA and neighbour-joining phylogenetic analysis, Asf1 fungal isolate could display closely-related to the genus of Aspergillus. The complete sequence designated Asf1 Inu2 gene was successfully obtained via rapid-amplification of cDNA ends-polymerase chain reaction (RACE-PCR). A 2.3 kb DNA fragment encoding endoinulinase, inu2, from Asf1 fungal isolate includes an open reading frame of 1,552 bp with calculated molecular weight of 55,954.1 Da and signal peptide sequence of 23 amino acids. The deduced amino acid sequence of the Asf1 inu2 displayed 97, 96, 69 and 22% identities to that of A. ficuum inu2, A. niger inuB, P. purpurogenum and K. marxianus, respectively. Phylogenetic analysis showed that fungal endo- and exo-inulinases have indepently evolved with the respective hydrolytic activities toward terminal and internal β-(2 → 1)-fructofuranosidic linkages in inulin.